The Pros and Cons of Using Algal Polysaccharides as Prebiotics - Gotteland, Martin; Riveros, Karla; Gasaly, Naschla; Carcamo, Constanza; Magne, Fabien; Liabeuf, Gianella; Beattie, Alejandra; Rosenfeld, Sebastián (Frontiers in Nutrition, 2020)
Macroalgae stand out for their high content of dietary fiber (30-75%). These include fucoidan, agar, carrageenan, ulvan, laminaran and alginate as soluble fiber. The interest for using these polysaccharides as prebiotics is currently growing, due to their potential effects on gut microbiota (GM). Pre-clinical studies show that the non-sulfated polysaccharides, alginate and laminaran, are well fermented by GM, promoting the formation of short chain fatty acids (SCFAs) including butyrate, and preventing that of harmful putrefactive compounds. Alginate increases Bacteroides, Bifidobacterium, and Lactobacillus species while laminaran mostly stimulates Bacteroides. Results with sulfated PS are more questionable. Agarans are poorly fermentable but agarose-oligosaccharides exhibit an interesting prebiotic potential, increasing butyrate-producing bacteria and SCFAs. Though carrageenan-oligosaccharides are also fermented, their use is currently limited due to safety concerns. Regarding fucoidan, only one study reports SCFAs production of, suggesting that it is poorly fermented. Its effect on GM does not indicate a clear pattern, making difficult to conclude whether it is beneficial or not. Notably, the fucoidan impact on H2S production has not been evaluated, though studies report it increases the sulfate-reducing bacteria Desulfovibrio. Ulvan is badly fermented by the GM and some studies show that part of its sulfate is dissimilated to H2S, which could affect colonic mitochondrial function. Accordingly, these results question the use of fucoidan, carrageenan and ulvan as prebiotic while they support that of laminaran, alginate and agaro-oligosaccharides. However, the realization of clinical trials is necessary to confirm such prebiotic properties.